Comparison between single-muscle evaluation and cross-sectional area muscle evaluation for predicting the prognosis in patients with oral squamous cell carcinoma: a retrospective cohort study - Takayama, Hirotaka; Yoshimura, Takuya; Suzuki, Hajime; Hirano, Yuka; Tezuka, Masahiro; Ishida, Takayuki; Ishihata, Kiyohide; Amitani, Marie; Amitani, Haruka; Nakamura, Yasunori; Imamura, Yasushi; Inui, Akio; et al. (Frontiers in Oncology, 2024)
Introduction: The most effective method of assessing sarcopenia has yet to be determined, whether by single muscle or by whole muscle segmentation. The purpose of this study was to compare the prognostic value of these two methods using computed tomography (CT) images in patients with oral squamous cell carcinoma (OSCC). Materials and Methods: Sex-and age-adjusted Cox proportional hazards models were employed for each parameter of sarcopenia related to overall survival, diseasefree survival, and disease-specific survival. Harrell's concordance index was calculated for each model to assess discriminatory power. Results: In this study including 165 patients, a significant correlation was found between the CT-based assessment of individual muscles and their crosssectional area. Single muscle assessments showed slightly higher discriminatory power in survival outcomes compared to whole muscle assessments, but the difference was not statistically significant, as indicated by overlapping confidence intervals for the C-index between assessments. To further validate our measurements, we classified patients into two groups based on intramuscular adipose tissue content (P-IMAC) of the spinous process muscle. Analysis showed that the higher the P-IMAC value, the poorer the survival outcome. Conclusions: Our findings indicate a slight advantage of single-muscle over whole-muscle assessment in prognostic evaluation, but the difference between the two methods is not conclusive. Both assessment methods provide valuable prognostic information for patients with OSCC, and further studies involving larger, independent cohorts are needed to clarify the potential advantage of one method over the other in the prognostic assessment of sarcopenia in OSCC.